Una nueva variedad de Styrax argenteus (Styracaceae) del NE de Querétaro (México) - Carranza González, Eleazar (Instituto de Ecología, A.C., 1993)
Styrax argenteus var. parvifolius is described as a new variety from the northeastern part of the state of Queretaro, Mexico. The new variety was found growing in two localities in relatively small oak forest areas. It differs from other known varieties of S. argenteus in having smaller leaves, in stellate trichomes closely overlapping on the lower leaf surface, in larger flowers, and in the cymose inflorescence.